Fluid Flow Investigation through Small Turbodrill for Optimal Performance - Mokaramian, Amir; Rasouli, Vamegh; Cavanough, Gary (Canadian Center of Science and Education, 2013)
Basic design methodology for a new small multistage Turbodrill (turbine down hole motor) optimized for small size Coiled Tube (CT) Turbodrilling system for deep hard rocks mineral exploration drilling is presented. Turbodrill is a type of axial turbomachinery which has multistage of stators and rotors. It converts the hydraulic power provided by the drilling fluid (pumped from surface) to mechanical power through turbine motor. For the first time, new small diameter (5-6 cm OD) water Turbodrill with high optimum rotation speed of higher than 2,000 revolutions per minute (rpm) were designed through comprehensive numerical simulation analyses. The results of numerical simulations (Computational Fluid Dynamics (CFD)) for turbodrill stage performance analysis with asymmetric blade’s profiles on stator and rotor, with different flow rates and rotation speeds are reported. This follows by Fluid-Structural Interaction (FSI) analyses for this small size turbodrill in which the finite element analyses of the stresses are performed based on the pressure distributions calculated from the CFD modeling. As a result, based on the sensitivity analysis, optimum operational and design parameters are proposed for gaining the required rotation speed and torque for hard rocks drilling.